Decadal comparison (1950–2020) of benthic marine flora from Central and Southern Vietnam - Belous, Oksana S.; Titlyanov, Eduard A.; Titlyanova, Tamara V. (Phytotaxa, 2021)
The benthic flora of Central and Southern Vietnam and its historical changes between 1950 and 2020 were studied. Three collections were compared: collection A (1950–1970), collection B (1980–2000) and collection С (2000–2020). In all collections (1950–2020), a total of 702 macroalgal taxa and their forms have been found, including 386 red (55%), 142 brown (20%) and 174 green (25%) algal taxa. A comparison of the collections has shown significant changes in species compositions of the marine flora during the period (the maximum similarity of the benthic flora of the three compared collections was about 63%). In each taxonomic group of macrophytes, there was a proportional replacement of some species by others. It is suggested that the revealed decadal changes in the marine flora of Central and Southern Vietnam are natural, periodic (seasonal, annual or perennial) and regulated by internal factors of the ecosystem.